2004
DOI: 10.1086/421703
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of Sabin Poliovirus Type 3 Containing the Nucleotide 472 Uracil‐to‐Cytosine Point Mutation after Administration of Oral Poliovirus Vaccine

Abstract: A uracil-to-cytosine point mutation at nucleotide (nt) 472 of Sabin oral poliovirus vaccine (OPV) type 3 is found in conjunction with vaccine-associated paralytic poliomyelitis (VAPP). Direct RNA extraction and mutant analysis by polymerase chain reaction and restriction enzyme cleavage were used to identify this point mutation in clinical samples. A total of 238 stool samples were obtained from 28 healthy infants for 6 weeks after OPV vaccination. More than 25% of infants shed OPV3 in the week after vaccinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…These data demonstrate increased reversion of OPV type 3 in stool samples over time, consistent with previous studies (20). This finding may indicate a large amount of revertant virus in communities using OPV and, along with the data indicating prolonged shedding of OPV3, may predict an increased risk of developing VAPP, particularly if immunity to polio declines as eradication efforts move forward.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…These data demonstrate increased reversion of OPV type 3 in stool samples over time, consistent with previous studies (20). This finding may indicate a large amount of revertant virus in communities using OPV and, along with the data indicating prolonged shedding of OPV3, may predict an increased risk of developing VAPP, particularly if immunity to polio declines as eradication efforts move forward.…”
Section: Discussionsupporting
confidence: 90%
“…These back-mutations of OPV occur during replication within the human gut (28). A previous study in our laboratory investigating OPV3 shedding and reversion demonstrated a bimodal shedding pattern of attenuated and revertant viruses in accordance with the selective pressure favoring the reversion of OPV3 (20). Among U.S. infants who received OPV followed by IPV, we observed high OPV3 shedding rates, which peaked on day 3 to 4 after vaccination and rose again during the second week after vaccination.…”
supporting
confidence: 60%
See 3 more Smart Citations